Soft X‐ray varied‐line‐spacing gratings fabricated by near‐field holography using an electron beam lithography‐written phase mask. (16th August 2019) - Lin, Dakui; Liu, Zhengkun; Dietrich, Kay; Sokolov, Andréy; Sertsu, Mewael Giday; Zhou, Hongjun; Huo, Tonglin; Kroker, Stefanie; Chen, Huoyao; Qiu, Keqiang; Xu, Xiangdong; Schäfers, Franz; et al.
Abstract : A method comprising near‐field holography with an electron beam lithography‐written phase mask was developed herein. Soft X‐ray varied‐line‐spacing gratings with a central groove density greater than 3000 lines mm −1 were fabricated using this method. Abstract : A fabrication method comprising near‐field holography (NFH) with an electron beam lithography (EBL)‐written phase mask was developed to fabricate soft X‐ray varied‐line‐spacing gratings (VLSGs). An EBL‐written phase mask with an area of 52 mm × 30 mm and a central line density greater than 3000 lines mm −1 was used. The introduction of the EBL‐written phase mask substantially simplified the NFH optics for pattern transfer. The characterization of the groove density distribution and diffraction efficiency of the fabricated VLSGs indicates that the EBL–NFH method is feasible and promising for achieving high‐accuracy groove density distributions with corresponding image properties. Vertical stray light is suppressed in the soft X‐ray spectral range.